Rambu Solo and the Social Dynamics of Toraja Ethnic Muslims in Palopo, Indonesia - Nuryani; Saifur Rahman; Susi Susanti (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
This is exploratory and constructionist research since it focuses on the Rambu Solo tradition and the social dynamics of the Toraja ethnic community in Lare-Lare Village. The problems proposed include how the Rambu Solo procession takes place and the way this tradition affects the social dynamics of the Toraja ethnic community. This research is qualitative since it uses a phenomenological approach. Data were collected through observation, interview, and documentation techniques. The results showed that, First, the procession of the Rambu Solo death traditional ceremony in Lare-Lare Village passes through several stages including the pre-implementation, implementation, and the post-implementation. In the pre-implementation, the Toraja ethnic community forms a committee and prepares Lakkian with Lantang as a resting place for guests. A Rante (funeral) procession is carried out in the middle of the tongkonan traditional house, including Ma'tudan Mebalun (decorating the corpse like a bride), Ma'rato (decorating the coffin), Ma'papengkalao Alang (lowering the corpse into the barn to be buried), Ma'palao/Ma'pasonglo (delivering the corpse from the tongkonan to the burial area called Lakkian), traditional art performances of Ma'pasilaga Tedong and Ma'Badong (fighting buffalo), and Ma'tinggoro Tedong (slaughtering buffalo) at the implementation stage. In the post-implementation, the committee is disbanded and the ceremonial facilities are dismantled followed by the Ma'pakendek Tanduk Tedong tradition (raising a buffalo horn to the front of the tongkonan). This buffalo horn ornament symbolizes the economic capacity of the owner. Second, the implementation of Rambu Solo causes positive and negative impacts on the Toraja ethnic community since it has experienced a shift in social elements. The positive impact of implementing this traditional ceremony is to become a unifier between distant families and to develop cultural elements outside the home. Meanwhile, the negative impact is the potential for eroding kinship ties due to problems of family economic resilience dealing with the Rambu Solo tradition.